PERAN MEDIA SEMPOA SEBAGAI ALAT BANTU STIMULASI KEMAMPUAN BERHITUNG SISWA - Amala Bilqis Ahmad (Al-Fikru : Jurnal Pendidikan Dan Sains, 2021)
Sempoa is one of the media to help stimulate students' numeracy skills. The purpose of writing this article is motivated by the existence of various student problems with mental arithmetic, namely the ability to count quickly and thoroughly, so that the interest in learning mathematics feels less than optimal, even though there are many benefits of achievement that can be seen and felt both in the long and short term. Among other things, training memory, concentration, and fine motor development of children. Increasing mathematics learning achievement in schools, especially in elementary schools, can be successful and maximally if supported by effective tools from the teacher. The use of the abacus counting aid includes factors that affect learning achievement that come from outside the student, especially on the subject of arithmetic in improving numeracy skills. Keywords: sempoa, stimulation, arithmetic, achievement